Downfield-NOE-suppressed amide-CEST-MRI at 7 Tesla provides a unique contrast in human glioblastoma - Zaiss, Moritz; Paech, Daniel; Burth, Sina; Vollmuth, Philipp; Wick, Wolfgang; Bendszus, Martin; Schlemmer, Heinz-Peter; Ladd, Mark E.; Bachert, Peter; Radbruch, Alexander (Magnetic resonance in medicine, 2017)
Purpose The chemical exchange saturation transfer (CEST) effect observed in brain tissue in vivo at the frequency offset 3.5 ppm downfield of water was assigned to amide protons of the protein backbone. Obeying a base-catalyzed exchange process such an amide-CEST effect would correlate with intracellular pH and protein concentration, correlations that are highly interesting for cancer diagnosis. However, recent experiments suggested that, besides the known aliphatic relayed-nuclear Overhauser effect (rNOE) upfield of water, an additional downfield rNOE is apparent in vivo resonating as well around +3.5 ppm. In this study, we present further evidence for the underlying downfield-rNOE signal, and we propose a first method that suppresses the downfield-rNOE contribution to the amide-CEST contrast. Thus, an isolated amide-CEST effect depending mainly on amide proton concentration and pH is generated. Methods The isolation of the exchange mediated amide proton effect was investigated in protein model-solutions and tissue lysates and successfully applied to in vivo CEST images of 11 glioblastoma patients. Results Comparison with gadolinium contrast enhancing longitudinal relaxation time-weighted images revealed that the downfield-rNOE-suppressed amide-CEST contrast forms a unique contrast that delineates tumor regions and show remarkable overlap with the gadolinium contrast enhancement. Conclusion Thus, suppression of the downfield rNOE contribution might be the important step to yield the amide proton CEST contrast originally aimed at. Magn Reson Med 77:196-208, 2017. © 2016 Wiley Periodicals, Inc.